KONSEP KEADILAN TRANSISIONAL DALAM PERSPEKTIF ISLAM - Hakim, Abdul Aziz (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
The article discusses about transitional justice, either in its concept asphilosophy values or extrajuridicial institutional mechanics which havebeen practiced in the world today, especially in Indonesia. The articlestudies about some fundamental questions. They are about should thesociety punish their past or they should let the past exists, or what shouldthe society do for some criminal had been done in the past, and how doesthe Islamic law philosophy regard this concept. The important essencefrom the transitional justice in the article is the victims of the hardhuman rights criminals which happened in the past can get a justice assoon as possible when the country in a transition period. Giving justicefor the victims is also an important education for the society to knowthe dark history of the country which can’t be repated. The meaning oftransitional justice in the Islamic law can be understood as meaningof peace (islah) in the context which is regaerded that the transitionaljustice is the law and its own.